OPTIMALISASI EKSTRAKURIKULER KALIGRAFI DASAR DALAM PENGEMBANGAN KETERAMPILAN MENULIS BAHASA ARAB MA AL FATAH BANJARNEGARA - Akhmad Syaifudin; Rifqi Aulia Rahman; Noor Aziz (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to describe the implementation and examine the supporting and inhibiting factors in optimizing basic calligraphy extracurricular activities for developing Arabic writing skills at MA Al Fatah Banjarnegara. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results show that the basic calligraphy extracurricular activity has effectively served as a medium for developing students’ Arabic writing skills, both in terms of letter formation, writing consistency, and calligraphic aesthetics. The supporting factors for the success of this activity include students’ interest, the guidance of competent instructors, and a supportive school environment. Meanwhile, the inhibiting factors consist of limited facilities and infrastructure as well as restricted implementation time. Therefore, optimizing the basic calligraphy extracurricular activity is essential as a strategy to enhance the quality of students’ Arabic writing skills at MA Al Fatah Banjarnegara.